Christian Personalism and Democratic Capitalism - Bayer, Richard C. (Horizons, 1994)
In his recent works Michael Novak offers an affirmation of "democratic capitalism" based on a Christian personalist perspective. Novak's scholarship has received increasing attention since the collapse of communism in Eastern Europe, and particularly since the recent encyclical Centesimus Annus. In that encyclical John Paul II offered a qualified affirmation of market economies. This article addresses an important question: to what extent can a Christian personalist social theory be used to offer an affirmation of a market economy, and how might it offer vision and constructive critique? I initiate a creative dialogue between the personalism of Emmanuel Mounier and Michael Novak's presentation of democratic capitalism. I argue that Novak has shed important light on the positive moral aspects of a market system, but I identify and emphasize the important remaining areas for moral concern.